Business model for financially sustainable electric vehicle charging station using EV charging financial analysis tool - Sapkota, Dilli Prasad; Pokharel, Govind Raj; Bhattarai, Nawraj; Rai, Pratap Jung (Journal of Innovations in Engineering Education, 2021)
Electric Vehicles (EVs) is an emerging field in transport sector. For Nepal, this is the golden opportunity to decrease petroleum oil consumption and creating another electricity demand area for future surplus electricity. There are various challenges which hinder the growth of EV adoption. Unavailability of sufficient public charging station is one of the major barriers. This gap brings a new business sector. This paper presents a business model for public charging station using EV charging financial analysis tool. The three potential partners that can collaborate in this project are owner-operator partner, private sector partners and public sector partner. Financial analysis is performed for three different scenarios. Discounted Cash Flow (DCF) method is used to calculate the financial parameters such as NPV, IRR and DPP for all partners in three different scenarios. In the first scenario, charging station along exist, without any government subsidy and indirect revenue sources. Only owner operator exists in first scenario. NPV stand at -$63,590, IRR and DPP are unavailable. Only government subsidy exists in second scenario. In this case, for owner operator and public sector partner, all three financial parameter shows infeasibility of project. For private sector partner, NPV is -$34,756, IRR and DPP are not available. Last scenario includes indirect revenue sources along with government subsidy. For owner operator, NPV stand at +$53,614, IRR is 17.7% and DPP is 6 year. Similarly, for private sector partner, NPV is positive, IRR is 10% and 7 year of DPP. For public sector, the project is in breakeven zone.